Role of percutaneous thermal ablation in cancer treatment - Ahmad, Doha Jamal; Alyami, Amal Yahea; Alasker, Abdullah Ahmed; Fallatah, Kholoud Bakur; AlReshan, Reshan Mane; Althuwaybi, Meshari Tael; Alhabes, Fawzyah Salem; Alnefaie, Bader Bandar; Alzahrany, Ahmed Mosa; Alshehri, Hiaallah Ali; Hethwell, Saeed Ahmad (International Journal Of Community Medicine And Public Health, 2021)
The main aim of using thermal ablation strategies is to eliminate the targeted malignant cells within a specific volume. However, it should be noted that some researchers have reported the potential limitations of some of these techniques. On the other hand, more updated investigations indicated that these limitations could be overcome by the adjuvant use of other management modalities as chemotherapy. Many limitations have been reported with the modality, including the prolonged therapeutic time. Therefore, cryoablation and microwave ablation techniques were introduced in the literature as safe and efficacious modalities that overcame the limitations of the radiofrequency technique. Overall, percutaneous thermal ablation is associated with favorable outcomes and should be used in clinical settings due to the various advantages that have been reported for the modality, in addition to being less invasive.